Norwegian “Digital Border Defense” and Competence for the Unforeseen: A Grounded Theory Approach - Boe, Ole; Torgersen, Glenn-Egil (Frontiers in Psychology, 2018)
Strategic Competence Leadership (SCL) is a tool meant to ensure that the Norwegian Armed Forces Cyber Defence (NAFCD) has the necessary expertise to cope with current and future unforeseen events. This is necessary in order to develop a better digital border defence against digital threats from different state or non-state actors. Unforeseen cyber incidents include for instance “zero-days” attacks and similar severe threats. The goal of the SCL in the NAFCD is the development of a reliable “Cyber Resilience”. In the present study, we examine how the concept of SCL is understood and carried out on the different leadership and managerial levels in the NAFCD. Our research problem was how well prepared the NAFCD is for SCL and competence development for future competence needs, especially in relation to unforeseen events? Semi-structured interviews and document analyses of governance documents were used in the present study. The Strategic Didactic Model for the Unforeseen was used to construct nine research questions that were then given to the participants. The nine questions were sorted under three categories: organizational structures, competence development and needs, and plans, handling and communication. Fourteen leaders at different levels in the NAFCD participated in the study. Our main finding was that high-level (n=4) and low-level (n=10) participants differed in their views on SCL. As for unforeseen events, both levels shared the opinion that the NAFCD can cope with a low level of didactical degrees of the unforeseen (the degree to which the management has the competence to facilitate for adequate exercises for the different hierarchical levels in the organization, i.e. sudden unknown cyber-attacks). However, no common understanding of the term SCL was found among the participants. Interaction was interpreted to be very important to the participants, and they used professional networks to a high degree. In addition, unofficial lines of communication were very frequently used in relation to human resource exchange and development. By creating a common understanding within the NAFCD regarding the concept of SCL, it will be possible to improve the Norwegian digital border defence against unforeseen events.